Membangun Kepercayaan Diri Anak Berkebutuhan Khusus di Lingkungan Pendidikan Inklusif - Fadilah, Umi Faizatul; Sa’diah, Halimatus (MASALIQ, 2025)
Inclusive education provides opportunities for children with special needs to study in regular schools, but they often face challenges in social interaction. Building self-confidence is very important for their development. Madrasah Aliyah Negeri 4 Banyuwangi implements inclusive education, although some students with special needs lack self-confidence. This research aims to explore the application of Cognitive Behavioral Therapy (CBT) techniques to increase their self-confidence. This research uses qualitative case study type research. Data collection techniques use observation, interviews and documentation. The technical data analysis carried out is data collection, data presentation and drawing conclusions. The results of the study showed that many ABK faced difficulties in interacting with classmates, caused by fear of rejection and inability to communicate. The application of CBT in the counseling process resulted in positive changes, although not yet fully optimal, with ABK starting to feel more comfortable and open in interacting. A supportive social environment, such as family, friends, and school, has also been shown to play an important role in increasing ABK's self-confidence. This study emphasizes the importance of environmental support in helping ABK feel accepted and appreciated, which can ultimately increase their self-confidence in social life.